EKSAMINASI PUTUSAN PENGADILAN AGAMA DALAM STUDI KASUS PUTUSAN PA PEMATANG SIANTAR NOMOR 0030/PDT.G/2015/PA.PST - Betty Kurnia Rahayu (Fakultas Hukum Universitas Narotama, 2022)
Examination of decisions is a process of examination, so examination of judicial decisions can be interpreted as examining court decisions and judges whose task is to try a case. In this case, it concerns the distribution of joint assets in a divorce case in which the joint assets are controlled by one of the parties who is now called the defendant. Joint assets have been regulated in Article 35 of the Marriage Law, known as joint assets. And article 53 of the Marriage Law is a method of dividing property in a marriage. The distribution of joint assets according to the Islamic Law Compilation must be divided equally between the two or ½ part for each husband and wife. Therefore, the judge decided several points for married couples in judging in order to carry out justice Keywords: Employment Relations Decision, Decidendi Ratio